2019
DOI: 10.1007/s11187-019-00304-z
|View full text |Cite
|
Sign up to set email alerts
|

Do employees’ generational cohorts influence corporate venturing? A multilevel analysis

Abstract: Organizations are facing an interesting phenomenon in the composition of their workforce: the concurrence of multiple age generations that demand suitable strategies regarding work design, job satisfaction, and incentives. Ongoing entrepreneurship and strategic management debates require a better understanding of the relationship between workplace generational cohorts' configurations and organizational performance. We propose a conceptual model for understanding how a diversified workforce influences some dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 134 publications
(224 reference statements)
0
17
0
3
Order By: Relevance
“…Given the nature of the graduates' occupational choice, the intensive/exploitation of skills such as the identification of ideas/opportunities will be different. A general assumption is that paid employee does not necessarily exploit the skills of identification/generation of business opportunities as part of their paid employment, except for intrapreneurs who were not considered in this study (Guerrero et al , 2019a). Self-employees tend to use these skills but with lower intensity than graduates who decided to become academic entrepreneurs (Wright et al , 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the nature of the graduates' occupational choice, the intensive/exploitation of skills such as the identification of ideas/opportunities will be different. A general assumption is that paid employee does not necessarily exploit the skills of identification/generation of business opportunities as part of their paid employment, except for intrapreneurs who were not considered in this study (Guerrero et al , 2019a). Self-employees tend to use these skills but with lower intensity than graduates who decided to become academic entrepreneurs (Wright et al , 2017).…”
Section: Resultsmentioning
confidence: 99%
“…By analysing academic entrepreneurs and self-employed profiles, it is essential to understand that self-employed individuals try to do everything themselves for security, while academic entrepreneurs know that they cannot do or control everything, and therefore they delegate responsibilities. However, those profiles could have a similar level of independence because both are their bosses (Ilouga et al , 2014; Sieger; Monsen, 2015; Guerrero et al , 2019a). Our findings are aligned to extant studies that showed the preferences of occupational decision-making based on the degree of independence/autonomy (Douglas and Shepherd, 2000, 2002; Shane et al , 2003; Segal et al , 2005; Ilouga et al , 2014; Sieger; Monsen, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of the increasing interest in the entrepreneurial phenomenon, an extensive number of studies have been conducted on specific groups: young people [56], seniors [57], women [51], and groups at risk of exclusion through social innovation initiatives [58], as well as on social entrepreneurship projects [59] and by geographical area, as can be seen in the GEM national reports.…”
Section: Literature Reviewmentioning
confidence: 99%